Allonychus querci BAKER & PRITCHARD, 1962 (ACARINA: TETRANYCHIDAE): NOVO REPRESENTANTE DA FAUNA BRASILEIRA - Paschoal, Adilson D. (REVISTA DE AGRICULTURA, 2016)
Allonychus querci BAKER & PRITCHARD, 1962 (ACARINA: TETRANYCHIDAE): NOVO REPRESENTANTE DA FAUNA BRASILEIRA